Utilization of Localized Surface Plasmon Resonance of Silver Nanoparticles for ‎the Spectrophotometric Estimation of Amlodipine and Hydrochlorothiazide (Baghdad Science Journal, 2024)
A potent long-acting calcium channel blockers is amlodipine. Patient with high blood pressure can take it to treat high blood pressure, angina pectoris, and reduce the risk of stroke. Hydrochlorothiazide, a diuretic, is used to treat edema and hypertension. Additionally, it is used to treat certain types of diabetes, hyperglycemia and hypokalemia. These drugs are widely available in the market and are commonly used orally. Therefore, a rapid, accurate, and inexpensive method for the determination of amlodipine and hydrochlorothiazide was developed and validated. This method is based on the ability of these drugs to reduce Ag +1 to Ag 0 by forming silver nanoparticles (AgNPs) in the presence of sodium dodecyl sulfate as a stabilizing agent .Significant surface plasmon resonance of synthesized nanoparticles was observed at 418 and 420 nm wavelengths which was used for quantitative spectrophotometric determination of amlodipine and hydrochlorothiazide .The linear concentration ranges for amlodipine and hydrochlorothiazide were 0.5-28 and 0.8-6 µg mL-1, with detection limits of 0.442 and 0.128 µg mL-1. The proposed method successfully determined amlodipine and hydrochlorothiazide in pure and commercial formulation.